PENGARUH KINERJA LINGKUNGAN DAN PENGUNGKAPAN LINGKUNGAN TERHADAP NILAI PERUSAHAAN (Studi Empiris pada Perusahaan Sektor Energi dan Basic Materials yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2021) - Desti Rohana Sagala; Rr. Karlina Aprilia Kusumadewi (Diponegoro Journal of Accounting, 2023)
The objective of this research is to analyze the impact of environmental performance and environmental disclosure on firm value in the energy and basic materials sectors listed on the Indonesian Stock Exchange from 2017 to 2021. The dependent variable used in this study is firm value. The independent variables used are environmental performance and environmental disclosure. The control variables used to maintain the relationship between dependent variable and independent variables are firm size and leverage. The research uses secondary data from annual reports, sustainability reports, and financial reports of companies in the energy and basic materials sectors listed on the Indonesian Stock Exchange from 2017 to 2021. The sample selection method is purposive sampling with a number of specific criteria. The sample for this research consisted of 90 companies. Panel data regression analysis is the analysis used to test hypotheses in this research. The results of this research show that environmental performance has a significant positive impact on the firm's value, while environmental disclosure has no impact on the firm's value.